Peran Lembaga Internasional dalam Menjamin Akses Obat Esensial: Peluang dan Tantangan di Negara Berkembang - Sari, Septi Purnama; Hidayatullah, Yusuf; Febrianti, Siska; Mery (Pharmaceutical Journal, 2025)
Access to essential medicines is a critical component in ensuring the right to  health, yet it remains a major challenge in developing countries. Economic disparities,  patent monopolies, fragile supply chains, and inadequate distribution infrastructure have left large populations without access to safe, effective, and affordable treatment. This  study aims to analyze the strategic roles of international organizations such as WHO,  UNICEF, and Gavi, in expanding access to essential medicines, while also identifying  associated opportunities and challenges. A systematic literature review was conducted  using peer-reviewed journals, official reports, and current policy documents. The findings  indicate that WHO contributes through global standard setting and drug prequalification;  UNICEF focuses on vaccine procurement and distribution; and Gavi drives innovative  financing and global partnerships. Nevertheless, significant challenges persist, including  intellectual property constraints, dependence on imported raw materials, circulation of  falsified drugs, and sustainability issues in post-donor settings. Strategic opportunities  include cross-agency collaboration, digital technology adoption, and strengthening of  local production capacity. This study underscores the importance of aligning national  policies with international support to develop an equitable and sustainable pharmaceutical  system. Access to essential medicines must be recognized as a shared global  responsibility within the framework of human rights and global solidarity.